Prognostic Biomarkers of Sarcoidosis: A Comparative Study of Serum Chitotriosidase, ACE, Lysozyme, and KL-6 - Bergantini, Laura (Dis Markers, 2019)
PURPOSE: Sarcoidosis is a systemic granulomatous disease with unknown etiology. Many clinical presentations have been reported, and acute disease needs to be distinguished from subacute and chronic disease. The unpredictable clinical course of the disease prompted us to evaluate the clinical utility of biomarker serum detection in sarcoidosis follow-up. METHODS: Serum concentrations of chitotriosidase, ACE, KL-6, and lysozyme were analyzed by different methods in a population of 74 sarcoidosis patients (46 on steroid therapy at sampling) regularly monitored at Siena Sarcoidosis Regional Referral Centre and in a group of controls with the aim of comparing their contribution to clinical management of sarcoidosis patients. RESULTS: KL-6 concentrations were significantly elevated in sarcoidosis patients with lung fibrosis and were significantly correlated with DLco and CPI score, while chitotriosidase was significantly higher in patients with extrapulmonary localizations. With a cut-off value of 303.5 IU/ml, KL-6 showed the best sensitivity (78%), while chitotriosidase reported the best specificity (85%) among the biomarkers. CONCLUSIONS: KL-6 is a reliable biomarker of fibrotic lung involvement in sarcoidosis patients. Among biomarkers, KL-6 showed the best sensitivity and serum chitotriosidase the best specificity, even in patients on chronic steroid therapy, and seemed to correlate with extrapulmonary localizations.